Tactical Coordination-Based Decision Making for Unmanned Combat Aerial Vehicles Maneuvering in Within-Visual-Range Air Combat - Yidong Liu; Dali Ding; Mulai Tan; Yuequn Luo; Ning Li; Huan Zhou (Aerospace)
Targeting the autonomous decision-making problem of unmanned combat aerial vehicles (UCAVs) in a two-versus-one (2v1) within-visual-range (WVR) air combat scenario, this paper proposes a maneuver decision-making method based on tactical coordination. First, a coordinated situation assessment model is designed, which subdivides the air combat situation into optimization-driven and tactical coordinated situations. The former combines missile attack zone calculation and trajectory prediction to optimize the control quantity of a single aircraft, while the latter uses fuzzy logic to analyze the overall situation of the three aircraft to drive tactical selection. Second, a decision-making model based on a hierarchical expert system is constructed, establishing a hierarchical decision-making framework with a UCAV-coordinated combat knowledge base. The coordinated situation assessment results are used to match corresponding tactics and maneuver control quantities. Finally, an improved particle swarm optimization algorithm (I-PSO) is proposed, which enhances the optimization ability and real-time performance through the design of local social factor iterative components and adaptive adjustment of inertia weights. Air combat simulations in four different scenarios verify the effectiveness and superiority of the proposed decision-making method. The results show that the method can achieve autonomous decision making in dynamic air combat. Compared with decision-making methods based on optimization algorithms and differential games, the win rate is increased by about 17% and 18%, respectively, and the single-step decision-making time is less than 0.02 s, demonstrating high real-time performance and win rate. This research provides new ideas and methods for the autonomous decision making of UCAVs in complex air combat scenarios.